Validation of novel biomarkers for colorectal cancer detection and production of novel antibodies against E-selectin ligands - Zoppi, Roberta (2019)
In 2018, colorectal cancer (CRC) remains the second deadliest kind of cancer with 881,00 deaths of the 1.8 million new cases. Late stages detection is more likely to develop recurrences, even after treatment, leading to the necessity to create a new system to early stages detection. Thus, understanding the biology of the cancer and biomarker discovery are important steps in cancer research. Several studies on cancer-associated glycosylation revealed that aberrant glycosylation is a universal feature in various steps of malignant transformation and tumour progression. Aberrant glycosylation is associated with poor survival, cancer progression, and metastasis, such as overexpression of Thomsen-nouvelle (Tn)-, T-, and sialyl-T (sT) antigens. Main carriers of sT- and sTn-antigens were identified as the mucin MUC1 and CD44v6. On the other hand, the Lewis antigens and their sialylated derives (Lex/sLex and Lea/sLeA) are the most prominent cancer-associated epitopes on both glycoproteins and glycolipids, since their overexpression is related to CRC malignant transformations and may lead to increased tumour cell adhesion and motility, thereby resulting in metastasis. The project aims to discover new potential biomarkers for CRC early detection and to evaluate the therapeutic potential of antibodies against CRC-associated antigens, namely against Lewis antigens and Thomsen-nouvelle (Tn)-, T-, and sialyl-T (sT) antigens. For the same reason glycoproteins, such as MUC1, CAE and CD44 will be studied for the development of novel monoclonal antibody production. After biomarker validation, hybridoma technology has been chosen to produce novel antibodies against, sLe and/or CD44, immunizing the mice directly with cancer cell lines proteins. The hybridoma against CD44 show staining against CD44 and sLex/a and further screening must be performed. The second hybridoma line against sLe antigens also shows positivity against different total cell lysate of CRC cells. Two clones have been selected for further characterization. The clones will be validated either for CRC early diagnosis or CRC treatment potential.